2014
DOI: 10.1021/np500439u
|View full text |Cite
|
Sign up to set email alerts
|

Oxidized Derivatives of Macroline, Sarpagine, and Pleiocarpamine Alkaloids from Alstonia angustifolia

Abstract: A total of 20 new indole alkaloids comprising mainly oxidized derivatives of macroline- (including alstofonidine, a macroline indole incorporating a butyrolactone ring-F), pleiocarpamine-, and sarpagine-type alkaloids were isolated from the bark and leaf extracts of Alstonia angustifolia. The structures and relative configurations of these alkaloids were determined using NMR and MS analyses and in some instances confirmed by X-ray diffraction analyses. Alkaloids 3, 7, 35, and 41 showed moderate to weak activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
46
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 28 publications
4
46
0
Order By: Relevance
“…47 Macrocarpine A–C ( 1 – 3 ) were isolated from the bark extract of Alstonia macrophylla in 2004. 8 Several other alkaloids of the same series, macrocarpine D ( 4 ) and macrocarpine E–H ( 5 – 8 ), were isolated in 2014 from the stem-bark and leaf extracts of A. macrophylla and A. angustifolia respectively by Kam et al 9,10 All of these macroline type indole alkaloids, macrocarpine A–H ( 1 – 8 ) share the common feature of a β -methyl substituent at the C-19 position. This is a distinct difference from earlier Alstonia alkaloids isolated by LeQuesne and Schmid.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…47 Macrocarpine A–C ( 1 – 3 ) were isolated from the bark extract of Alstonia macrophylla in 2004. 8 Several other alkaloids of the same series, macrocarpine D ( 4 ) and macrocarpine E–H ( 5 – 8 ), were isolated in 2014 from the stem-bark and leaf extracts of A. macrophylla and A. angustifolia respectively by Kam et al 9,10 All of these macroline type indole alkaloids, macrocarpine A–H ( 1 – 8 ) share the common feature of a β -methyl substituent at the C-19 position. This is a distinct difference from earlier Alstonia alkaloids isolated by LeQuesne and Schmid.…”
mentioning
confidence: 99%
“…5,7 To date, around 30 alkaloids of the sarpagine/macroline/ajmaline family, which bear a diastereomeric methyl function at C-19 have been isolated. 4,11 Macroline related alkaloids N (4)-methyl- N (4),21-secotalpinine ( 9 ) 8,12 , N (4)-methyltalpinine ( 10 ) 12 , and 19-epitalcarpine ( 11 ) 10 as well as sarpagine related alkaloids macrosalhine chloride ( 12 ) 13 , and deoxyperaksine ( 13 ) 14 also possess the C-19 methyl substitution. Among these, 11 and 13 have a diastereomeric α -methyl group at C-19.…”
mentioning
confidence: 99%
“…Alstolactone A ( 79 ), O -acetyltalpinine ( 43 ), talpinine ( 146 ), although not cytotoxic themselves, exhibited weak activity (IC 50 values: 40–60 μM) in reversing multi-drug resistance in a vincristine-resistant KB/VJ300 cell line, in the presence of 0.12 μM vincristine. 70 In the same study alstonerine ( 145 ) showed potent multi-drug resistance reversal activity (IC 50 = 10 μM) in a KB/VJ300 cell line in the presence of 0.12 μM vincristine. The bisindole alkaloids perhentinine ( 121 ) and villalstonine ( 150 ) exhibited moderate cytotoxicity against a P388 murine leukemia cell line.…”
Section: Pharmacologymentioning
confidence: 92%
“…[1] Subsequently, the same group isolated alstofolinine B (2) from the bark and leaf extracts of Alstonia angustifolia. [2] The methoxy group present on indole A-ring of 2 only differentiates this molecule from alstofolinine A (1). Extensive 2D NMR analysis established the structure and relative configurations of these alkaloids ( Figure 1).…”
mentioning
confidence: 97%
“…It was proposed that the pentacyclic alkaloid alstonerine (3) is a putative origin for both alstofolinines A (1) and B (2). [2] From a stereochemistry standpoint, these pentacyclic molecules, 1 and 2 possess four stereocenters, notably the γ-lactone E-ring is a syn-fused and in an exo-cyclic fashion to the bridged indole macroline substructure. γ-Lactone (E-ring) embedded into the macroline alkaloids is the first of its kind.…”
mentioning
confidence: 99%